IMPROVING COUNTING SKILLS THROUGH NUMBER BLOCK GAMES FOR GROUP B CHILDREN AT TK SEULANGA DAYA - Helnita; Suwaibah; Rossiana Br Ginting; Ahmad Nasriadi; Riza Oktariana (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This study is based on the less than optimal cognitive development in early childhood in group B of Seulanga Daya Kindergarten due to the monotonous learning process. This should make teachers provide active and creative learning materials by playing, children can think more critically and logically like what children do, namely using symbols, classifying objects and sorting objects. This study aims to improve counting skills through number block games in group B children at Seulanga Daya Kindergarten. This type of research is a qualitative Classroom Action Research. The subjects in this study were group B children as many as 20 children. Based on the results of the research that has been carried out, it shows that the Pre-Cycle obtained a value of 35%, Cycle I 70%, and Cycle II 92%. It can be interpreted that the ability to count through the game of number blocks in group B children at Seulanga Daya kindergarten has increased. So that the percentage increase in children's counting ability has reached the success indicator